Combination Therapy of Metformin and Statin May Decrease Hepatocellular Carcinoma Among Diabetic Patients in Asia. Issue 24 (June 2015) - Chen, Hsin-Hung; Lin, Ming-Chia; Muo, Chih-Hsin; Yeh, Su-Yin; Sung, Fung-Chang; Kao, Chia-Hung; Camafort-Babkowski., Miguel
<x xml:space="preserve">Abstract</x> Abstract Previous studies have shown that metformin or statins may decrease hepatocellular carcinoma (HCC) in diabetic patients. Accordingly, this article evaluates whether combination therapy may further reduce HCC. Newly diagnosed type 2 diabetes mellitus (DM) patients, excluding those with history of malignancy prior to the date of DM diagnosis, were recruited to a DM cohort. DM patients developed HCC as the cancer cohort and the date for HCC diagnosis as index date. Non-cancer cohort was frequency matched with 4:1 according to age, sex, DM-year, and index date as case group from DM cohort. Patients who were treated with statins showed a 63% decreased risk of HCC (odds ratio [OR] = 0.37; 95% confidence interval [CI] = 0.27–0.49). Patients who consumed simvastatin, atorvastatin, or rosuvastatin significantly decreased risk for HCC (OR = 0.32, 0.31, and 0.22; 95% CI = 0.18–0.58, 0.19–0.52, and 0.08–0.61, respectively). Metformin combinations with simvastatin, atorvastatin, or rosuvastatin may decrease HCC (OR = 0.30, 0.30, and 0.24; 95% CI = 0.15–0.59, 0.16–0.54, and 0.08–0.70, respectively). The comorbidities for HCC were decreased by consuming simvastatin and atorvastatin (OR = 0.31 and 0.29; 95% CI = 0.14–0.67 and 0.15–0.57, respectively). Only combination therapy of metformin and simvastatin may significantly decreased HCC comorbidities (OR = 0.26; 95% CI = 0.11–0.60) in our study. In Asia, not all metformin combinations with statins may reduce the incidence of HCC and not all of this kind of combination therapy may decrease the HCC comorbidities.